A implicação política da faculdade de pensamento na filosofia de Hannah Arendt - Fabio Abreu dos Passos (2008)
The central theme of this research is emphasizing the political implication of the faculty of thought in Hannah Arendts philosophy. Thus, our intention is to show that in boundary situations, in which the public space does not exist, the resistance, phenomenon produced by thinking, consists as a kind of political action, as it boost the plural motivation, from its exemplarity. The resistance, analysed in this perspective, that is, on the way of giving examples, will arrive at the realization of plural motivation, making that the thinking may come of the we, that is, the public sphere, constituted by human plurality. In other words, what we intend to prove by reasoning is that in boundary situations, which the past stops to throw light on future, the intellect walks in obscurity (TOCQUEVILLE, 1969: 361), the resistancepoints, from then its example, to the fact that we can not forget our responsibility with by ourselves and by world itself